Original paperAssessment of the degree of expression of oncoprotein p53 in squamous and basal cell carcinomas - Bąkowska, Aneta; Czyż, Piotr; Kaszuba, Aleksandra; Miękoś-Zydek, Beata; Skrzypczyk, Mariusz; Kijowski, Robert (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Non-melanoma skin cancers (NMSC) are among the most common cancers in people. It is estimated that skin cancers develop in about 50% of the population above 65, with the peak of incidence between 70 and 79. It is thought that development of the neoplastic process is the result of accumulation over a period of time of genetic errors appearing in the cell’s genome. As a result it stops being subjected to mechanisms controlling its growth, differentiation and process of apoptosis. Oncogenes and suppressing genes that are expressed by expression of proteins p53, bcl-2 or proliferation marker Ki-67 play a significant role in the development and progression of NMSC. Protein p53 selectively activates the transcription of many genes, which causes arrest of the cell growth cycle in the late G1 phase and prolongation of the DNA-repair time or apoptosis. In the study the assessment of the degree of expression of oncoprotein p53 according to histological type of NMSC in 34 patients (age 47-87) with the diagnosis of basal cell carcinoma (BCC) and in 10 patients (age 55-78) with squamous cell carcinoma (SCC) was made. The material for histopathology and immunohistochemistry was taken from tumour tissues from the patients after surgical removal in Świętokrzyskie Oncology Centre. The immunoperoxidase method using the visualizing system LSAB PLUS (Dako – Denmark) was used to assess the expression of the product of suppressor gene p53 in neoplastic tissue. The results of the trial were statistically described with variant analysis, Fisher’s test and Student’s t-test. The expression of oncoprotein p53 measured by percentage of reactive tissue was significantly higher in SCC than in BCC, confirming the more aggressive character of these skin tumours.